Tecnologias digitais nos projetos pedagógicos dos cursos de licenciatura em matemática : percepções dos docentes sobre suas formações e atuações - Coral, Eduardo Abel (2023)
This study sought to answer the questions of the guiding question about what contributions do the curricular subjects on Digital Technologies that make up the Pedagogical Projects of Mathematics degree courses in Brazil bring to teacher training? The General Objective of the research was to understand the contributions of the curricular subjects on DT that make up the PPC of mathematics degrees in Brazil for teacher training. The research carried out used the PPC as official documents linked to Brazilian HEIs that provided professional training in mathematics within a specific context and interviews given by Brazilian teachers who work or worked at HEIs, as mathematics teacher trainers. The research was developed based on the quantitative analysis of documents, producing data that was used to build an overview of the current training of new mathematics teachers and the use of DT in this training. These data served to qualify the participants' choices, as well as to provide support for the development of a semi-structured interview questionnaire consistent with the objectives of this study. The interviews were analyzed according to the methodology known as Discursive Textual Analysis. From this analysis, four categories emerged, namely: use of Digital Technologies during emergency remote teaching; Digital Technologies as a transversal theme to mandatory, including continued training; the use of Digital Technologies as a means of improving learning is not yet a consensus; and use of Digital Technologies at the discretion of the teacher, regardless of what the syllabi of the Course Pedagogical Projects deal with. Based on the understandings elaborated, it was possible to reformulate the initial thesis and defend the thesis that “there are subjects about, and with, Digital Technologies incorporated into the Pedagogical Projects of Current Brazilian Mathematics Degree Courses and which can provide contributions to the training of new teachers that will potentially act in basic education, when these are taught under relevant pedagogical aspects.” The development of this study contributed to expanding the understanding of the professional performance of teacher trainers within the scope of Brazilian mathematics degrees, in addition to expanding perspectives on the use of DT in this educational context and the importance of permanent discussions on the elaboration, structuring and updating the Pedagogical Projects of these Courses.